Analysis of air curtain system flow field and droplet drift characteristics of high clearance sprayer based on CFD - Song, Yangyang (International Journal of Agricultural and Biological Engineering, 2024)
High clearance sprayers are widely used in field operations because of their high ground clearance and good passing performance, which can solve the problem of spraying high-stalk crops in the middle and late stages. In this paper, an air curtain system was designed to address the phenomenon of droplet drift in the operation of high clearance sprayers. Based onstatic pressure recovery theory, the design and optimization of the flow velocity at the outlet of the air curtain were carried out. Using SolidWorks software for modeling, ICEM CFD software to divide meshes, and Fluent software to solve the problem, the air duct model was simulated and drift characteristics of droplets were studied through continuous phase and discrete phase coupling calculation. Using three-factor and three-level orthogonal test, the optimal solution of the model was obtained as follows: a spray pressure of 0.4 MPa, a horizontal wind speed of 2 m/s, a fan frequency of 40 Hz, and a droplet drift rate of 9.38%. According to the degree of influence from large to small, the factors are arranged as follows: horizontal wind speed, fan frequency, and spray pressure. An air curtain system test prototype and a droplet drift rate test platform was built, and flow rate of the air duct outlet and the droplet drift rate were tested under multiple working conditions. Experimental results showed that: when the horizontal wind speed was 2 m/s and 4 m/s, the droplet drift rates were the lowest when frequency was 25 Hz and 35 Hz, respectively, which were 13.65% and 23.88%, respectively. When the horizontal wind speed was 6 m/s and 8 m/s, the droplet drift rates reached the lowest when frequency was 45 Hz, which were 27.02% and 29.78%, respectively. When the horizontal wind speed was 2 m/s, 4 m/s, 6 m/s, and 8 m/s, the droplet drift rates of the optimal auxiliary airflow were reduced by 17.33%, 34.51%, 50.62%, and 67.54%, respectively. Experiments show that the optimal auxiliary air velocity changes when the horizontal wind speed is different. Keywords: air curtain system, CFD numerical simulation, droplet drift rate, multiple working conditions DOI: 10.25165/j.ijabe.20241706.8253 Citation: Song Y Y. Analysis of air curtain system flow field and droplet drift characteristics of high clearance sprayer based on CFD. Int J Agric & Biol Eng, 2024; 17(6): 38–45.